False-Positive Cystoscopic Diagnosis of Ureteral Obstruction After Hysterectomy Due to a Nonfunctional Kidney. Issue 3 (September 2015) - Kundu, Kuhali; Martin, Laura; Henderson, Sean; Metro, Michael; Rodgers, Shuchi; Goldberg, Jay
Abstract : BACKGROUND: An estimated 0.2% of the population may have a unilateral nonfunctional kidney. This pre-existing condition may lead to the mistaken presumption that a ureteral injury has occurred when performing cystoscopy after hysterectomy. CASES: Two cases are presented in which cystoscopy to confirm ureteral patency after hysterectomy was performed in patients with pre-existing unknown nonfunctional kidneys. These false-positive findings resulted in additional operative time, additional cost, and unnecessary surgical exploration. CONCLUSION: Cystoscopy to confirm ureteral patency after hysterectomy may lead to an incorrect presumption of a ureteral injury in patients with a pre-existing nonfunctional kidney. Abstract : When cystoscopy reveals apparent ureteral obstruction immediately after hysterectomy, the possibility of a nonfunctional kidney should be considered before surgical exploration.